2000
DOI: 10.1351/pac200072030447
|View full text |Cite
|
Sign up to set email alerts
|

Species-selective determination of selenium compounds in biological materials (Technical Report)

Abstract: Republication or reproduction of this report or its storage and/or dissemination by electronic means is permitted without the need for formal IUPAC permission on condition that an acknowledgmentMembership of the Commission during the preparation of this report (1997)(1998)(1999) Species-selective determination of selenium compounds in biological materials (Technical Report)Abstract: There is substantial evidence of the complexity of selenium speciation in living organisms and of the importance of the selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0
7

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(81 citation statements)
references
References 78 publications
0
74
0
7
Order By: Relevance
“…[4][5][6] Selenoproteins contain selenium in the form of selenocysteinyl residues; proteins that contain this element in the form of selenomethionyl residues are not formally classified as selenoproteins. Analytical techniques for the determination of selenium species have been reviewed, [7][8][9][10] but many methods have only been applied to a few commercially available standards. Table 1 shows some selenium species that have attracted nutritional, clinical and bioanalytical attention.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Selenoproteins contain selenium in the form of selenocysteinyl residues; proteins that contain this element in the form of selenomethionyl residues are not formally classified as selenoproteins. Analytical techniques for the determination of selenium species have been reviewed, [7][8][9][10] but many methods have only been applied to a few commercially available standards. Table 1 shows some selenium species that have attracted nutritional, clinical and bioanalytical attention.…”
Section: Introductionmentioning
confidence: 99%
“…These selonoproteins or Se-containing proteins are efficiently fractionated by gel electrophoresis. Size-exclusion liquid chromatography is the fractionation method mostly used in combination with nonradioactive detection methods like ICP-MS, but with the limitation of the low chromatographic resolution typical for size-exclusion [9]. In a previous paper, we reported the use of gel electrophoresis for the fractionation of proteins in combination with electrothermal vaporization-ICP-MS for the detection of Se, with the advantages of a higher resolution than obtainable with size-exclusion and the quantitative aspect of the method [10].…”
Section: Introductionmentioning
confidence: 99%
“…The HPLC͞inductively coupled argon plasma massspectrometry (ICP-MS) and HPLC͞electrospray ionization tandem mass-spectrometry (ESI-MS͞MS) methods have been used efficiently for the speciation of bio-trace elements (15,16), and our recent work indicated that the major urinary metabolite (hepatic metabolite B) is a selenosugar, Se-methyl-N-acetylselenohexosamine (17). In the present study, we determined the chemical structures of two selenosugars and proposed their biological roles as intermediates in the metabolism of Se leading to urinary excretion.…”
mentioning
confidence: 99%